STRATEGY OF SPIRITUAL RENEWAL IN UZBEKISTAN - Sobirovich, Turdiyev Bexruz; Sharipovna, Abdullayeva Feruza; Barotovna, Maxmudova Nigora; Akhmatovna, Gulova Anorgul; qizi, Samadova Sarvinoz Samad (International Journal of Psychosocial Rehabilitation, 2020)
This article is dedicated to the reforms of the spiritual and educational processes implemented within the framework of the Strategy of Actions in Uzbekistan, their role in the life of society and practical recommendations of Uzbekistan on the spiritual development of the world community. It is also scientifically argued that the moral reforms have helped us achieve effective results in our country’s reform strategy.